Comparative Analysis of Topical Insulin Dressing Vs Normal Saline Dressing in Diabetic Foot Ulcers Wound Healing - Lyba Ghayour, Faiza Irem, Baseerullah, Adnan Riaz, Abrar Ashraf Ali, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Foot ulcers, a dangerous and common consequence of diabetes, currently have no particular therapeutic options. There are many topical medicines and ointments available for wound management.It has been observed that topical insulin dressings effectiveness is better than other dressings. Aim: To determine the effectiveness of Topical Insulin dressing VS Normal saline dressing in diabetic ulcer in terms of rate of reduction in ulcer area in days and need for re debridement Methods: A randomized control trial conducted in Emergency and Outdoor Department of South Surgical ward, Mayo Hospital, Lahore.Study was carried out insix months from Sept 2022 to March 2023. A total 86 patients fulfilling the selection criteria presented to outdoor/Emergency of South surgical department of general surgery of Mayo Hospital, Lahore falling in Wagner’s classification I and IIwere enrolled in the study after taking informed consent. Patients were divided by method of random allocation (lottery method) to Group A (Topical insulin dressing) and Group B (Normal saline soaked dressing) after explaining the procedure. Rate of reduction in ulcer area was measured in days. Need of re-debridement was labeled as ‘yes’ if patient needed re-debridement or ‘no’ if patient did not need re-debridement. Results: Baseline mean wound area in Group A and in Group B was 34.87±29.23 cm2 and 27.45±24.00cm2. After 2 weeks the wound area reduced to 9.35±10.75 cm2 and 7.33±9.29 cm2 respectively. Mean days for rate of reduction in ulcer areas was significantly less in Group A patients than in Group B patients (p-value<0.001). Rate of re-debridement for Group B patients was significantly higher than patients in Group A (Group A: 18.6% vs Group B: 46.5%, p-value= 0.006). Improved wound healing will reduce need of redebridement and minor to major foot amputations. Conclusion: This study concludes that topical insulin dressing is more effective as that of normal saline soaked dressing for management of diabetic ulcer in terms of rate of reduction in ulcer area in term of days and need for re debridement. Keywords: Effectiveness, Normal saline Dressing, Topical Insulin dressing, Diabetic foot ulcer, Ulcer area, Re-debridement.